Chitosan as a coupling agent for phosphate glass fibre/polycaprolactone composites - Tan, Chao; Rudd, Chris; Parsons, Andrew; Sharmin, Nusrat; Zhang, Junxiao; Chen, Wanru; Ahmed, Ifty (MDPI Multidisciplinary Digital Publishing Institute, 2018)
This study shows that chitosan (CS) could be highly useful as a coupling agent in phosphate glass fibre/polycaprolactone (PGF/PCL) composites, as it improved the interfacial shear strength by up to 78%. PGFs of the composition 45P2O5–5B2O3–5Na2O–24CaO–10MgO–11Fe2O3 were dip-coated with CS (with a degree of deacetylation >80%) dissolved in acetic acid solution (2% v/v). Different CS concentrations (3–9 g L−1) and coating processes were investigated. Tensile and fragmentation tests were conducted to obtain the mechanical properties of the single fibres and interfacial properties of the PGF/PCL composites, respectively. It was observed that post-cleaning, the treated fibres had their tensile strength reduced by around 20%; however, the CS-coated fibres experienced strength increases of up to 1.1–11.5%. TGA and SEM analyses were used to confirm the presence of CS on the fibre surface. FTIR, Raman, and X-ray photoelectron spectroscopy (XPS) analyses further confirmed the presence of CS and indicated the protonation of CS amine groups. Moreover, the nitrogen spectrum of XPS demonstrated a minimum threshold of CS coating required to provide an improved interface.